2019
DOI: 10.3390/agronomy9100627
|View full text |Cite
|
Sign up to set email alerts
|

Hydroponic Production of Reduced-Potassium Swiss Chard and Spinach: A Feasible Agronomic Approach to Tailoring Vegetables for Chronic Kidney Disease Patients

Abstract: Tailored foods are specifically suitable for target groups of people with particular nutritional needs. Although most research on tailored foods has been focused on increasing the nutrient content in plant tissues (biofortification), in populations with specific physiological conditions, it is recommended to reduce the uptake of specific nutrients in order to improve their health. People affected by chronic kidney disease (CKD) must limit their consumption of vegetables because of the generally high potassium … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 28 publications
6
18
0
Order By: Relevance
“…This low Ca bioaccessibility could be related to oxalate presence; in fact, this compound can combine with Ca and others minerals to form insoluble compounds, reducing their availability [ 34 ]. Similar results about Ca and K bioaccessibility were found in different leafy vegetables [ 40 , 41 ]. These elements are essential for human health, to maintain the electrolyte balance involved in many different bodily processes including bone growth, muscle and nerve functionality, and also to prevent osteoporosis diseases, as described by several authors [ 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 ].…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…This low Ca bioaccessibility could be related to oxalate presence; in fact, this compound can combine with Ca and others minerals to form insoluble compounds, reducing their availability [ 34 ]. Similar results about Ca and K bioaccessibility were found in different leafy vegetables [ 40 , 41 ]. These elements are essential for human health, to maintain the electrolyte balance involved in many different bodily processes including bone growth, muscle and nerve functionality, and also to prevent osteoporosis diseases, as described by several authors [ 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 ].…”
Section: Resultssupporting
confidence: 80%
“…An ion exchange chromatography (Dionex DX120, Dionex Corporation, Sunnyvale, CA, USA) was performed with a conductivity detector, as reported by D’Imperio et al [ 41 ]. For the determination of anion contents, 0.3 g OFI dry sample was treated with a solution of 3.5 mM (Na 2 CO 3 ) and 1 mM (NaHCO 3 ) for 30 min in orbital shaker, 50 rpm, at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…A promising approach is biofortification. It consists in increasing the content or the bioavailability of nutrients, e.g., vitamins (mainly folate and vitamin A), minerals (calcium, iron, silicon, boron, iodine, zinc, and selenium) and bioactive compounds (polyphenols and carotenoids) in plant foods, in order to ameliorate their nutritional profile in terms of their contribution to satisfy the Recommended Daily Allowance (RDA) for nutrients ( White and Broadley, 2009 ; D’Imperio et al, 2016 , 2019 , 2020 ; Montesano et al, 2016 ; Smoleń et al, 2017 ; Gonnella et al, 2019 ). This approach allows improving the nutritional quality of different crops by using several strategies, such as genetic engineering, conventional breeding, and agronomic techniques ( Carvalho and Vasconcelos, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…The total phenol (TP) content was determined according to the Folin-Ciocalteu method by using the extraction methods reported by D'Imperio et al, (2019) [27]. Briefly, 200 mg of lyophilized sample were mixed with 10 mL of solvent mixture (MeOH:H 2 O:CH 3 COOH, 79:20:1% v/v/v).…”
Section: Extraction and Analysis Of Total Phenols Chlorophylls And Carotenoidsmentioning
confidence: 99%
“…Furthermore, by acting on the mineral composition of the NS, it is possible to increase or reduce the concentration of target ions in plant tissue to obtain tailored vegetables for specific nutritional requirements [21][22][23][24][25]. For example, some authors [26,27] reported the use of NS with different potassium (K) levels to obtain low-potassium vegetables suitable for people affected by chronic kidney disease. On the other hand, Gonnella et al,) [22] proposed the use of iodine-biofortified Brassica vegetables for preventing iodine (I) deficiency and related human disorders, while biofortification for silicon and calcium has been proposed to obtain vegetables suitable for women in premenopausal conditions [21][22][23].…”
Section: Introductionmentioning
confidence: 99%